Problem Based Learning and Student Creativity Development in Primary Education: Pembelajaran Berbasis Masalah dan Pengembangan Kreativitas Siswa di Pendidikan Dasar - Nggolaon, Mufida; Rahman, Abdul; Nuraini, Nuraini; Tadeko, Nurgan; Bulalong, Roberto Rolly (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Creativity is a fundamental 21st-century skill for elementary students, yet it remains relatively low due to teacher-centered learning practices. Specific Background: Observations in Grade 3 at SD Negeri 1 Tatura revealed limited student innovation, low confidence, and minimal active participation in problem-solving activities. Knowledge Gap: Previous studies largely focused on upper-grade students, used classroom action research, and rarely examined detailed subdimensions of creativity or specific school contexts. Aims: This study aims to examine the increase in student creativity through the implementation of the Problem Based Learning (PBL) model using a quasi-experimental design with pretest-posttest control groups. Results: Findings show a significant difference between experimental and control groups (sig. 0.007 < 0.05), with higher posttest mean scores in the experimental class (49.42) than the control class (38.08). However, N-gain results indicate low overall improvement (0.2152) and uneven development across creativity indicators, with fluency categorized as high (0.7368), flexibility and elaboration as moderate (0.5538; 0.4985), and originality as low (0.1955). Novelty: This study applies a quantitative experimental approach focusing on Grade 3 students and analyzes creativity through detailed subdimensions within a specific school context. Implications: PBL supports increased student creativity but requires optimization, continuous guidance, and strategic implementation to ensure balanced development across all creativity indicators. Highlights• Significant difference found between experimental and control group outcomes• Highest gain observed in idea generation compared to other dimensions• Uneven development identified across multiple creativity indicators KeywordsProblem Based Learning; Student Creativity; Primary School; Quasi Experimental Design; Creative Thinking